PROFIT EVALUATION OF MILKFISH DOWNSTREAM SUPPLY CHAIN FOR LOCAL MARKETS: SYSTEM DYNAMIC APPROACH - Ishardita Pambudi Tama; Agustina Eunike; Rahmi Yuniarti; Sugiono Sugiono (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Brawijaya, 2017)
Milkfish is an aquaculture product and has a role in supporting food security and nutrition in Indonesia. The reliability of milkfish farming will be able to increase the income of small and medium-scale farmers. Milkfish farmers in SMEs level experience problem of declining prices in the period of oversupply in farming. Moreover, the profit earning by the farmers tend to decrease time to time. This research was mapping the structure of milkfish downstream supply chain using system dynamic simulation. The first step in mapping process was identifying the actors in the milkfish downstream supply chain. The next stage was defining activities and variables that affect supply chain milkfish profit. The activities and variables were used to develop a causal loop diagram (CLD). Furthermore, stock and flow diagram was constructed based on CLD and used as system dynamic simulator of milkfish supply chain. The result of system dynamic simulation showed the profit obtained by each actor in milkfish supply chain and a total profit of the entire supply chain. The profit, gained by supply chain in the current configuration, during the period 2016-2020, is Rp72.615.608.004,00. According to the simulation result, the proposed scenario will be able to increase the profit of supply chain up to 27,58%.